Four types of Ca2+ signals in naive CD8+ cytotoxic T cells after stimulation with T cell agonists, partial agonists and antagonists. - Bachmann, M; Mariathasan, S; Bouchard, D; Speiser, D; Ohashi, P (1997)
Stimulation of T cells via the T cell receptor (TCR) leads to an increase intracellular in free Ca2+ levels ([Ca2+]i) and the activation of the MAP kinase signaling pathway. This study analyzes for the first time Ca2+ fluxes in naive cytotoxic T cells stimulated with full agonists, partial agonists, or antagonists. Four different types of Ca2+ responses could be observed. Full agonists triggered a strong and sustained increase in [Ca2+]i. In contrast, partial T cell agonists induced either a strong but transient Ca2+ flux or very low to no increases in [Ca2+]i, while T cell antagonists failed to induce any measurable Ca2+ flux. The ability of peptides to induce elevated [Ca2+]i perfectly paralleled their ability to trigger TCR internalization and T cell activation. Thus, stimulation of naive cytotoxic T cells with a panel of defined altered peptide ligands reveals a consistent picture, where Ca2+ fluxes predict agonist, partial agonist and antagonist properties of peptides.